Pengaruh Employee Stock Ownership Program Terhadap Average Abnormal Return Perusahaan Perbankan - Agung Suprayogi; Abdul Basyith (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2020)
This research was conducted to see the effect of the implementation of the Employee Stock Ownership Program on average abnormal returns of banking companies before and after applying ESOP and trading volume. The aim is to find out the difference in average abnormal return before and after applying the ESOP. The variable used in this study is average abnormal return. The period of this research event is 20 days, 10 days, 5 days and 1 day which are divided before and days after the date of application. This study examines banking companies that apply the Employee Stock Ownership Program listed on the Indonesia Stock Exchange so that data is obtained from trading in the company's stock price. The sampling criteria used a purposive sampling method in order to obtain 9 samples. The hypothesis method used in the normally distributed data is Paired Samples T-test. The result is that all average abnormal return periods both on the first and the last date of the ESOP application have a significant value >0.05, which means that the entire event period of the variable is proven to have no significant difference both before and after the banking company applies the Employee Stock Ownership Program.